ABF3 enhances drought tolerance via promoting ABA-induced stomatal closure by directly regulating ADF5 in Populus euphratica. (21st August 2020) - Yang, Yanli; Li, Hui-Guang; Wang, Jie; Wang, Hou-Ling; He, Fang; Su, Yanyan; Zhang, Ying; Feng, Cong-Hua; Niu, Mengxue; Li, Zhonghai; Liu, Chao; Yin, Weilun; et al.
Abstract : Poplar overexpressing the transcription factor gene PeABF3 showed enhanced sensitivity to exogenous ABA, especially in mediating control of stomatal aperture through regulating PeADF5, identifying a new strategy to improve plant drought tolerance. Abstract: Water availability is a main limiting factor for plant growth, development, and distribution throughout the world. Stomatal movement mediated by abscisic acid (ABA) is particularly important for drought adaptation, but the molecular mechanisms in trees are largely unclear. Here, we isolated an ABA-responsive element binding factor, PeABF3, in Populus euphratica . PeABF3 was preferentially expressed in the xylem and young leaves, and was induced by dehydration and ABA treatments. PeABF3 showed transactivation activity and was located in the nucleus. To study its functional mechanism in poplar responsive to drought stress, transgenic triploid white poplars ( Populus tomentosa 'YiXianCiZhu B385') overexpressing PeABF3 were generated. PeABF3 overexpression significantly enhanced stomatal sensitivity to exogenous ABA. When subjected to drought stress, PeABF3 overexpression maintained higher photosynthetic activity and promoted cell membrane integrity, resulting in increased water-use efficiency and enhanced drought tolerance compared with wild-type controls. Moreover, a yeast one-hybrid assay and an electrophoretic mobility shift assay revealed that PeABF3 activated the expression of Actin-Depolymerizing Factor-5 ( PeADF5 ) by directly binding to its promoter, promoting actin cytoskeleton remodeling and stomatal closure in poplar under drought stress. Taken together, our results indicate that PeABF3 enhances drought tolerance via promoting ABA-induced stomatal closure by directly regulating PeADF5 expression.